The effects of industrial training on students’ generic skills development - Rodzalan, Shazaitul Azreen; Mohamed Saat, Maisarah (Elsevier Science Ltd, 2012)
This conceptual paper reviews the underpinning theories and past literatures on generic skills in relation to industrial training attended by students in higher learning institutions. Subsequently, a number of hypotheses and a framework of generic skills development are proposed. Four generic skills discussed are communication skill, teamwork skill, critical thinking and problem solving and moral and professional ethics. The paper proposes that the development of these generic skills is influenced by or have some relationships with students’ demographic and motivation, as well as organizational characteristics and culture. The methodology of conducting this study is also illustrated.